2014
DOI: 10.15252/embj.201489468
|View full text |Cite
|
Sign up to set email alerts
|

The J anus transcription factor H ap X controls fungal adaptation to both iron starvation and iron excess

Abstract: Balance of physiological levels of iron is essential for every organism. In Aspergillus fumigatus and other fungal pathogens, the transcription factor HapX mediates adaptation to iron limitation and consequently virulence by repressing iron consumption and activating iron uptake. Here, we demonstrate that HapX is also essential for iron resistance via activating vacuolar iron storage. We identified HapX protein domains that are essential for HapX functions during either iron starvation or high-iron conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
187
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(202 citation statements)
references
References 56 publications
(113 reference statements)
13
187
2
Order By: Relevance
“…These findings suggest that the n-CRD represents a novel structural domain that likely functions as a conserved binding site for Fe/S cluster sensors in fungal stress-responsive regulators. Consistent with this conclusion, a recent study demonstrates that the CGFCX 5 CXC motif in Aspergillus fumigatus HapX is essential for activation of the A. fumigatus CCC1 homolog (41).…”
Section: Discussionsupporting
confidence: 55%
“…These findings suggest that the n-CRD represents a novel structural domain that likely functions as a conserved binding site for Fe/S cluster sensors in fungal stress-responsive regulators. Consistent with this conclusion, a recent study demonstrates that the CGFCX 5 CXC motif in Aspergillus fumigatus HapX is essential for activation of the A. fumigatus CCC1 homolog (41).…”
Section: Discussionsupporting
confidence: 55%
“…SreA represses expression of hapX during iron sufficiency and HapX represses sreA during iron starvation (7). Additionally, both SreA and HapX appear to be regulated post-translationally by iron, blocking HapX function and activating SreA function (8).…”
mentioning
confidence: 99%
“…Despite the SreA-mediated transcriptional repression of hapX during iron sufficiency, a very recent study surprisingly revealed that HapX is not only crucial for adaptation to iron starvation but also for coping with iron toxicity via activation of cccA, which encodes a vacuolar iron importer (8,9). Strikingly, the latter mode of gene activation not only requires CBC-HapX protein-protein interaction but also cooperative CBC-HapX binding of an evolutionarily conserved bipartite DNA motif within the cccA promoter.…”
mentioning
confidence: 99%
“…73 Attenuated virulence has also been reported in other strains of A. fumigatus with mutations in the siderophore synthesis pathway and with other mutations affecting iron metabolism, including HapX, AcuM, and AcuK. 72,[74][75][76] Taken together, these studies strongly suggest that the ability of A. fumigatus to acquire and utilize iron from the host is essential for pathogenicity. This hypothesis is supported by the observation that iron overload within HSCT patients is a risk factor for the development of IA.…”
Section: Mouse Model and Contribution To Virulence Virulence Factormentioning
confidence: 69%